Pertanian Organik: Konsep, Kinerja, Prospek, dan Kendala - Tri Bastuti Purwantini; nFN Sunarsih (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2019)
Organic agriculture grows rapidly both at national and global levels triggered by consumers’’ awareness of the dangers of synthetic chemicals in agriculture. Consumers are increasingly wise in choosing healthy, environmentally friendly food. The paper aims to describe the concept of organic agriculture and from international and national views, followed by an explanation of the development of organic agriculture in Indonesia. Discussion on the concept and development of organic agriculture in Indonesia covers the performance of organic agriculture development, programs, area, producers and markets. The results of the study indicate that Indonesia has considerable potential to compete in international markets of organic agriculture products albeit gradually. Institutions such as those of conventional agriculture, i.e. farmers’ groups, cooperatives, associations or corporations, are still very relevant to boost organic agriculture development. Organic agricultural products in the transition period are still pioneering the market. The community is the closest market accessible. Organic farming education should involve producers and consumers. AbstrakPertanian organik tumbuh pesat di tingkat nasional maupun global. Hal ini seiring peningkatan kesadaran konsumen terhadap bahaya bahan kimia sintetis dalam produk pertanian. Konsumen makin bijak dalam memilih bahan pangan yang aman bagi kesehatan dan ramah lingkungan. Tujuan makalah ini adalah untuk mendeskripsikan konsep pertanian organik menurut pandangan internasional maupun nasional, dilanjutkan dengan pemaparan perkembangan pertanian organik di Indonesia. Pembahasan tentang konsep dan perkembangan pertanian organik di Indonesia mencakup kinerja perkembangan pertanian organik, program, luas areal, produsen, dan pasar produk organik. Hasil kajian menunjukkan bahwa Indonesia memiliki potensi yang cukup besar untuk bersaing di pasar internasional walaupun secara bertahap. Secara kelembagaan pengembangan pertanian organik di Indonesia hampir sama dengan pertanian konvensional, seperti kelompok tani, koperasi, asosiasi, atau korporasi masih sangat relevan untuk digunakan sebagai pengembangan pertanian organik. Produk pertanian organik pada masa transisi masih merintis pasar dan biasanya komunitas menjadi pasar terdekat yang bisa dijangkau. Edukasi tentang pertanian organik perlu dilakukan pada kedua sisi, produsen dan konsumen.